ELECTRON-EMITTING DEVICE MANUFACTURING APPARATUS, SOLUTION INCLUDING METAL MICRO-PARTICLES, ELECTRON-EMITTING DEVICE, AND IMAGE DISPLAYING APPARATUS - SEKIYA TAKURO (2009)
In an electron-emitting device manufacturing apparatus for forming a surface conduction electron-emitting element by a conductive thin film, a discharge head of a piezo-jet type using a piezoelectric element has a diameter being equal to or less than phi25mum and jets a solution that includes metal micro-particle material for forming the conductive thin film, on the area between the electrodes, which are formed on a substrate of the electron-emitting device, as a droplet. A volatile component in a solution dot pattern is vaporized after the droplet is jetted on the substrate so that a solid content is remained on the substrate. The solution having micro-particle dispersed in liquid satisfies a relationship of 0.0002<=Dp/Do<=0.01 where Dp denotes a diameter of the metal micro-particle and Do denotes a diameter of the discharge opening.